Variation of atmospheric electric field measured at Vostok, Antarctica, during St. Patrick’s Day storms on 24th solar cycle - Victor, N. Jeni; Kamenetsky, A.V. Frank-; Manu, S.; Panneerselvam, C. (2017)
The influence of solar wind-magnetosphere interaction on the atmospheric electric field is investigated in connection with the two severe geomagnetic storms during 24th solar cycle. The observation was carried out at Vostok (78°270 S, 106°520 E), Antarctica, during 17–18 March 2013 and 17–18 March 2015. Two consecutive substorms were observed at Vostok during the main phase of geomagnetic storms, where the disturbed ionospheric current is antisunward in the morning sector (~04:00–10:00 UT) and sunward in the noon-afternoon sector (~11:00–16:00 UT). Interplanetary magnetic field (IMF) and solar wind interaction enhance the ionospheric potential, which in turn couple with Potential Gradient (PG) measured at ground level. Eventually, for the first time, the slope of ~1.0 Vm1 per kV has been demonstrated between Vostok PG and overhead ionospheric potential (Weimer_05) during intense (Kp = 8) geomagnetic perturbation. The linear relation between PG and overhead potential is highly significant on positive coupling, i.e., positive ΔPG changes, whereas the offset of ~25 V/m has been estimated with negative coupling. Ionospheric convection map from Super Dual Auroral Radar Network is more compatible with PG on positive coupling, and for negative changes of PG, radar observation is more consistent than the Weimer_05 model. Ionospheric electric potential from radar observation and empirical model is highly compromised when a polar cap is dominated by a single negative potential region associated with IMF By ≪ 0. It is inferred that superposed overhead ionospheric potential on Vostok PG is highly effective when IMF maintained a steady flow, whereas it is less significance for rapid changes of solar wind-IMF parameters.